2011
DOI: 10.3314/jjmm.52.153
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Screening, Isolation and Purification of a Fibrinolytic Protease from an Isolate (VK12) of Ganoderma Lucidum and Evaluation of its Antithrombotic Activity

Abstract: Antithrombotic activity of a protease purified from a medicinal mushroom, Ganoderma lucidum, has been evaluated platelet aggregation in vitro and pulmonary thrombosis in vivo. The purified protease exhibited concentration dependent inhibitory effects on platelet aggregation induced by ADP (adenosine diphosphate), with an IC(50) value of 2.4 mg/mL. The purified protease protected mice against thrombotic death or paralysis induced by collagen and epinephrine in a dose dependent manner when administered orally. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…These inhibitory effects may involve the release of intrinsic ADP from platelets or the metabolites of AA and PAF. Other research showed that purified ganoderma fibrinolytic protease protected mice against thrombotic death or paralysis induced by collagen and epinephrine and also activated the partial thromboplastin time (APTT) and thrombin time (TT) in rat platelets (Kumaran et al, 2011). The polysaccharide of ganoderma was also found to prolong the blood clotting and bleeding time in rats and decrease the thrombosis and fibrinogen level in blood plasma (Klupp et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These inhibitory effects may involve the release of intrinsic ADP from platelets or the metabolites of AA and PAF. Other research showed that purified ganoderma fibrinolytic protease protected mice against thrombotic death or paralysis induced by collagen and epinephrine and also activated the partial thromboplastin time (APTT) and thrombin time (TT) in rat platelets (Kumaran et al, 2011). The polysaccharide of ganoderma was also found to prolong the blood clotting and bleeding time in rats and decrease the thrombosis and fibrinogen level in blood plasma (Klupp et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The Ganoderma species contain several important bio-active compounds, including polysaccharides, triterpenoids, immunomodulatory peptides, amino acids, alkaloids, and so on [ 17 , 18 , 19 ]. These compounds present antitumor, immunomodulatory, anti-thrombosis, cholesterol regulation, anti-hyperglycemic and antibacterial activities [ 20 , 21 , 22 , 23 ]. Most studies are related to the pharmacological effects of the triterpenoids and polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…G. lucidum may have a mild antithrombotic effect itself in high doses and this could increase the effect of other anticoagulant or antiplatelet medications, including aspirin (Kumaran et al. 2011 ), resulting in an increased risk of bruising or bleeding. In patients taking other prescription medications, it is generally better to separate the intake of those medications and G. lucidum products by at least two hours in case there is any interference with drug absorption.…”
Section: Adverse Effectsmentioning
confidence: 99%